Tinjauan Kritis Proses Penyusunan Rencana Tata Ruang Desa: Kasus Desa Jepitu, Kabupaten Gunung Kidul, Provinsi Daerah Istimewa Yogyakarta - Ahmada, Syauqi; Swasto, Deva Fosterharoldas; Farabi, Jimly Al (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2023)
Spatial planning is an important policy in negotiating between increasing space requirements and existing space constraints. In the context of spatial planning at the village level, The Village Spatial Planning (VSP) can be one of solutions in solving spatial planning challenges in the scope of the village area. The existence of VSP has its pros and cons, due to the lack of empirical evidence on how village spatial planning should be done. This research aims to explain the background and process of preparing the VSP, as well as the factors that influence it based on inductive-qualitative approach. The research location was conducted in Jepitu Village, Gunung Kidul Regency, Yogyakarta Special Region Province. The consideration for choosing this location was due to various village management challenges that have the potential to impact space utilization, namely (1) Increasing the development of coastal tourism; (2) Southern Cross Road Program (SCRP); and (3) Village boundary issues related to the management of water resources. The data used are field observation data and in-depth interviews, and are supported by secondary data. The result of this research, there are internal factors and external factors that trigger the background for the preparation of the VSP. The internal factors consist of (1) Concerns of the Village Pamong; (2) Beach Tourism Area Management; (3) Economics; (4) Development Planning; and (5) Regional Mapping. The triggers from external factors, namely the presence of Supporting Agent. Meanwhile, the factors in the process of preparing the VSP, namely (1) Actors; (2) Community Participation; (3) Regional Mapping; and (5) Resistance. Based on the results of this study, VSP can be one of solution in solving various village area management challenges related to the provision spatial data on village boundaries and potentials to be used as a guide for village development planning.